A preliminary study of Augmented Musical Instruments for Study (AMIS) using research through design - Silva, Eduardo Santos; Cabral, Giordano Ribeiro Eulalio; Pereira, Rodrigo Mendes de Carvalho (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação Musical, 2021)
The emergence of Digital Musical Instruments (DMIs) in the computer music field has been providing new means of interaction with music performances. Particularly, with the advancements in the Internet of Things (IoT) area, there has been an increase in augmented musical instruments containing LEDs within their own bodies to support music learning. These instruments can help musicians by having the capabilities to display musical notes, chords and scales. This research uses research through design to present a preliminary study of some of the challenges related to the design of these instruments and attempts to provide some insights associated with their usability and development, particularly related to the development of an augmented acoustic guitar, the VioLED, developed alongside the company Daccord Music. The system provides three modes of operation: song mode, solo/improvising mode and animation mode. The preliminary results present challenges and obstacles pertinent to usability and development of these instruments identified in different iterations of design. These challenges are associated with areas such hardware-software co-design, usability, latency/jitter, energy consumption, etc.